One-year results from the FLXibility post-approval study: final real-world clinical outcomes with a next-generation left atrial appendage closure device. (19th May 2022) - Betts, TR; Grygier, M; Nielsen-Kudsk, JE; Schmitz, T; Sandri, M; Casu, G; Bergmann, M; Hildick-Smith, D; Christen, T; Allocco, DJ
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Boston Scientific Corporation, Marlborough, MA, USA Background: The WATCHMAN FLX left atrial appendage (LAA) closure device received CE-mark and FDA approval based on the results of the PINNACLE FLX IDE study, but evidence of outcomes with this next-generation device in everyday clinical practise is limited. Purpose: The FLXibility Post-Approval Study collected real-world data on patients implanted with a WATCHMAN FLX in a routine clinical practise. Methods: Patients were implanted with a WATCHMAN FLX per local standard of care, with a subsequent first follow-up visit from 45-120 days post-implant and a final follow-up at 1 year post procedure. A Clinical Event Committee adjudicated all major adverse events and TEE/CT imaging results were adjudicated by a core laboratory. Results: Among 300 patients enrolled at 17 centres in Europe, the mean age was 74.6±8.0 years, mean CHA2DS2-VASc score was 4.3±1.6, mean HAS-BLED score was 2.6±1.0, and 62.1% were male. The device was successfully implanted in 99.0% (297/300) of patients; 97.0% (289/298) required only 1 device for an implantation attempt and no patient required >2 devices. TEE was used for 78% of procedures and ICE for 22%. The post-implant medication regimen was DAPT for 87.3% (262/300). At first follow-up, among 170 patients with evaluable imaging, 87.6% (149/170) had no leak, 12.4% (21/170) had leak >0mm to ≤5mm with 16 (9.4%) of these <3mm, and no patient had leak >5mm, per core lab adjudication. At 1 year, 93.3% (280/300) patients had final follow-up or death. At final follow-up, 61% of patients were on a single antiplatelet medication, 21% were on DAPT, 6% were on a direct oral anticoagulation medication, and 12% were not taking any antiplatelet/anticoagulation medication. One-year all-cause mortality was 10.8% (32/295), among which 5.1% (15/295) were cardiovascular or unexplained. Disabling stroke occurred in 1.0% (3/295) of patients and nondisabling stroke also in 1.0% (3/295) of patients; all were nonfatal. No patient experienced a systemic embolism. Device-related thrombus was detected in 2.4% (7/295) patients. Pericardial effusion requiring surgery or pericardiocentesis occurred in 1.0% (3/295), with all of these events occurring in the first 7 days post-procedure. Cumulative BARC-3 or -5 bleeding occurred in 3.7% (11/300) of patients from 0 to 7 days, in 7.3% (22/300) at 6 months, and in 8.1% (24/295) patients at 1 year. One patient (0.3%) had a peri-procedural device embolisation, with no subsequent device embolisations or any device migration reported for any patient through 1 year. Conclusions: The WATCHMAN FLX device had excellent procedural success rates, with high effective LAA closure rates and low serious adverse event rates in everyday clinical practise.